The World Bank Group Outcome Orientation at the Country Level : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2020)
The World Bank Group’s success rests on its ability to help its client countries achieve the development outcomes they desire. This demands a strong outcome orientation at the country-level, defined as the Bank Group’s ability to generate feedback on what works, what does not, and why, use this feedback to adapt country programs, and boost contribution to development outcomes. This learning-focused evaluation provides a new vision of how to strengthen the Bank Group's outcome orientation in countries. IEG finds that the model of how the Bank Group aims for outcomes in its client countries is sound. However, the results system does not capture the Bank Group’s contribution to country outcomes well, as its reliance on metrics, attribution, and short time-boundedness does not suit the nature of country programs. While country teams practice adaptive management, the country-level results system does not effectively support them in doing so. The report makes concrete proposals on how to rethink the country-level results systems, its tool kit; the accountability principles that underlies the system; and the incentives for staff to learn from experience and prioritize development results.